2020
DOI: 10.1097/j.jcrs.0000000000000217
|View full text |Cite
|
Sign up to set email alerts
|

Visual outcomes of high-volume compared with low-volume manual small-incision cataract surgery in Nepal

Abstract: Purpose: To study whether manual small-incision cataract surgery (MSICS) in a high-volume setting gives acceptable postoperative visual outcomes. Settings: Geta Eye Hospital, Kailali, Nepal. Design: Single-center retrospective study. Methods: One-year records of all MSICS in adult patients without any other ocular comorbidity were analyzed retrospectively. Surgic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…These protocols have also been able to provide high quality outcomes, helping to decrease the prevalence of blindness and visual improvement in the province. [25, 28]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These protocols have also been able to provide high quality outcomes, helping to decrease the prevalence of blindness and visual improvement in the province. [25, 28]…”
Section: Discussionmentioning
confidence: 99%
“…These protocols have also been able to provide high quality outcomes, helping to decrease the prevalence of blindness and visual improvement in the province. [25,28] Despite this progress, cataract is still the main cause of blindness (36.4%) followed by non trachomatous corneal opacity (24.2%), glaucoma (21.2%), all other globe or CNS abnormality (9.1%), ARMD (6.1%), other posterior segment disease (3%). Again, cataract is the main cause in SVI (85.7%) and MVI (55.1%) category.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown postoperative endophthalmitis rates with MSICS are comparable to high-income countries using phacoemulsification. 20 The technical skills of an ophthalmic surgeon is another important factor in considering postoperative cataract surgery outcomes. A large cohort study observed that newly-qualified surgeons undertaking independent practice were 9 times more likely to have high complication rates (greater than 2%), including endophthalmitis, when compared to surgeons in their tenth year of practice.…”
Section: Discussionmentioning
confidence: 99%
“…Diminishing returns and statistically insignificant differences are seen beyond these arbitrary values otherwise. 20 Clinical audits are a method of ensuring that healthcare is provided in line with set standards. It allows care providers, as well as patients, know if a service is performing well, or if improvements can be made.…”
Section: Discussionmentioning
confidence: 99%